Proceedings of the 3rd International Conference on Higher Education Advances 2017
DOI: 10.4995/head17.2017.5172
|View full text |Cite
|
Sign up to set email alerts
|

Personal development, resilience theory and transition to university for 1st year students

Abstract: The study aimed to determine whether an outdoor orientation programme (OOP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Predictive models in the current study highlighted the importance of students establishing social connections and becoming more self-determined for building their resilience. Refining the behaviours that develop autonomy may liberate participants to self-regulate and develop concern for others; these are important qualities for new students to deal with difficulties encountered at university [4,6,7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Predictive models in the current study highlighted the importance of students establishing social connections and becoming more self-determined for building their resilience. Refining the behaviours that develop autonomy may liberate participants to self-regulate and develop concern for others; these are important qualities for new students to deal with difficulties encountered at university [4,6,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Starting university will require students to use self-discipline to manage their academic progress alongside a possible influx of stressors, including financial uncertainty, time constraints, establishing new relationships and conforming to new social norms [2,3]. Persistent exposure to combinations of stressors in an unfamiliar environment and without established social networks may make university inductees more vulnerable to psychological and physical health problems compared to other populations [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, they will meet new friends and lecturers which affect their social life during their time in the campus. A previous study by Pickard [1] mentioned about how the transformation of the latest level of education to the next level of education brings an individual to experience a certain obstacles as the mean of adaptation to multiple variables. Therefore, the students need to deal with those conditions well in order to be success in the college life.…”
Section: Introductionmentioning
confidence: 99%
“…The transition from High School to College challenges students to adjust or adapt to new experiences on campus. Poor adaptation and transition on campus can lead to poor student experiences and eventual dropout Pickard et al (2017). The research showed that students who dropped out in the first academic year had a low willingness and effort to learn and low persistence when faced with difficulties, often doubted their abilities, and felt less in control of their actions Ayala and Manzano (2018).…”
Section: Introductionmentioning
confidence: 99%